2019
DOI: 10.1039/c9ra03341f
|View full text |Cite
|
Sign up to set email alerts
|

Triazole-based novel bis Schiff base colorimetric and fluorescent turn-on dual chemosensor for Cu2+ and Pb2+: application to living cell imaging and molecular logic gates

Abstract: A novel triazole-based bis Schiff base colorimetric and fluorescent chemosensor (L) has been designed, synthesized and characterized. The chemo-sensor L shows its application potential in the detection of Cu2+ and Pb2+ in living cells and building molecular logic gate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 84 publications
(20 citation statements)
references
References 35 publications
1
19
0
Order By: Relevance
“…Dihydro phenylquinazolinone derivatives are an important class of compounds as inhibitors of cell multiplication and well known as antiarthritic and antispermatogenic drugs. 57,58 Herein, in continuation of our ongoing research on the recognition of different analytes using simple chemosensors, [59][60][61] we report a simple, easy to prepare, and cost effective colourimetric chemo-sensor, 3-[(E)-(2-hydroxybenzylidene)amino]-1,2-dihydro-2-phenylquinazolin-4(3H)-one (L), for the sensitive and selective detection of Ni 2+ and Cu 2+ ions and its copper complex for both the colourimetric and uorometric detection of CN À ions. The chemosensor L detected the presence of the cations Ni 2+ and Cu 2+ by both uorescence quenching and an instant change in colour from colourless to yellow, and its Cu 2+ complex detected CN À ions by uorescence enhancement and colour change from yellow to colourless.…”
Section: Introductionmentioning
confidence: 99%
“…Dihydro phenylquinazolinone derivatives are an important class of compounds as inhibitors of cell multiplication and well known as antiarthritic and antispermatogenic drugs. 57,58 Herein, in continuation of our ongoing research on the recognition of different analytes using simple chemosensors, [59][60][61] we report a simple, easy to prepare, and cost effective colourimetric chemo-sensor, 3-[(E)-(2-hydroxybenzylidene)amino]-1,2-dihydro-2-phenylquinazolin-4(3H)-one (L), for the sensitive and selective detection of Ni 2+ and Cu 2+ ions and its copper complex for both the colourimetric and uorometric detection of CN À ions. The chemosensor L detected the presence of the cations Ni 2+ and Cu 2+ by both uorescence quenching and an instant change in colour from colourless to yellow, and its Cu 2+ complex detected CN À ions by uorescence enhancement and colour change from yellow to colourless.…”
Section: Introductionmentioning
confidence: 99%
“…Charge transfer 2). 75 In methanol-tris buffer (1 : 1) medium, the free sensor displayed weak emission at 440 nm (l ex = 340 nm), attributed to the PET process from the triazole and imine moiety to the fluorophore. In the presence of Cu 2+ /Pb 2+ , the fluorescence spectrum of sensor 6 displayed an increase in emission intensity attributed to blockage of the PET process and strengthening of the ICT process.…”
Section: Intra/intermolecular Charge Transfer (Ict)mentioning
confidence: 99%
“…In our ongoing research we have already reported several multiple amides based [45], triazole based [46], dihydrazone based [47], dihydrophenylquinazolinone-based [48], thiosemicarbazone based [49], benzohydrazide based [50,51] chemosensors for Cu(II). Taking another step in the process of searching for suitable chemosensor we have focused on dihydrazone based 3 chemosensors.…”
Section: Introductionmentioning
confidence: 99%